Flexible Fiscal Rules and Countercyclical Fiscal Policy - Guerguil, Martine; Mandon, Pierre; Tapsoba, Rene. (Washington, D.C. : International Monetary Fund, 2016)
This paper assesses the impact of different types of flexible fiscal rules on the procyclicality of fiscal policy with propensity scores-matching techniques, thus mitigating traditional self-selection problems. It finds that not all fiscal rules have the same impact: the design matters. Specifically, investment-friendly rules reduce the procyclicality of both overall and investment spending. The effect appears stronger in bad times and when the rule is enacted at the national level. The introduction of escape clauses in fiscal rules does not seem to affect the cyclical stance of public spending. The inclusion of cyclical adjustment features in spending rules yields broadly similar results. The results are mixed for cyclically-adjusted budget balance rules: enacting the latter is associated with countercyclical movements in overall spending, but with procyclical changes in investment spending. Structural factors, such as past debt, the level of development, the volatility of terms of trade, natural resources endowment, government stability, and the legal enforcement and monitoring arrangements backing the rule also influence the link between fiscal rules and countercyclicality. The results are robust to a wide set of alternative specifications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet